1997
DOI: 10.1017/s0022149x00015972
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of helminths in rural scavenging poultry in Tanzania in relation to season and climate

Abstract: A cross-sectional study on the prevalence of helminths in rural scavenging poultry on six hundred adult chickens selected randomly from six villages in the Morogoro Region, Tanzania during the wet and the dry seasons, was conducted. The trachea and gastrointestinal tract of each bird were examined for the presence of parasites. All chickens were infected with one or several species of helminths, the average being 4.8 ±1.7 helminths per chicken during the wet season and 5.1 ± 1.8 during the dry season. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 3 publications
6
61
3
2
Order By: Relevance
“…Even though coproscopic examination is less sensitive to diagnose than adult worms count, high prevalence of parasite was observed, which indicates that GIT parasites were a problem in the study area and there was no experience of providing prophylactic measure to control helminths. Similar findings of A. galli and H. gallinarum followed by cestode spp were recorded by (Permin et al, 1997;Birhanu Mekibib et al, 2014), but high cestode spp followed by nematodes recovered by Irungu et al, (2004). Only A. galli spp and different cestode spp have been identified in semi-intensive management system at Debre Zeit agricultural research center by (Yacob Hailu and Hagos Ashenafi, 2013).…”
Section: Discussionsupporting
confidence: 65%
“…Even though coproscopic examination is less sensitive to diagnose than adult worms count, high prevalence of parasite was observed, which indicates that GIT parasites were a problem in the study area and there was no experience of providing prophylactic measure to control helminths. Similar findings of A. galli and H. gallinarum followed by cestode spp were recorded by (Permin et al, 1997;Birhanu Mekibib et al, 2014), but high cestode spp followed by nematodes recovered by Irungu et al, (2004). Only A. galli spp and different cestode spp have been identified in semi-intensive management system at Debre Zeit agricultural research center by (Yacob Hailu and Hagos Ashenafi, 2013).…”
Section: Discussionsupporting
confidence: 65%
“…However, higher prevalences of H. isolonche have been reported in other birds, such as the bowhite quail (Colinus virginianus), and the lesser prairie chicken (Tympanucus pallidicinctus) in the US , Moore et al 1986, and scavenging chickens in Africa (Permin et al 1997, Poulsen et al 2000, but with rather lower values than those observed for H. gallinarum when present.…”
Section: Discussionmentioning
confidence: 83%
“…The data that has been derived from 161 infected chickens out of 751 showed that the overall prevalence rate of 21.44 %, which is nearly equivalents to 20% in Switzerland reported by (Permin, 1997) less than 25.63% in Kenya by (Kaingu et al, 2010) 25.7% in Pakistan by (Sayyed et al, 2000) and 32.89% in Khartoun State, Sudan by (Hanan et al, 2005). But greater than 10.03% in Kenya by (Kimani et al, 1999) 7% in Germany, 3% in Bavaria according to (Permin, 1997).…”
Section: Discussionmentioning
confidence: 99%